Ethnophysics Analysis of the “Wiwit Padi” Tradition in Lamongan, East Java - Anggita Rusmaya; Putri Lintang Utami (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
This research explores the ethnophysical aspects embedded in the Wiwit Rice Tradition practiced by the agrarian community of Lamongan, East Java. The study aims to identify and analyze physics concepts manifested in traditional agricultural activities as part of Indonesia’s rich local wisdom. Using a qualitative descriptive approach, data were collected through literature studies, observations, and semi-structured interviews with local farmers and community elders. The findings reveal that the Wiwit Rice Tradition reflects several fundamental physics principles, including force, pressure, torque, friction, and heat transfer. For example, cutting rice stems using a sickle demonstrates the application of pressure and mechanical work, while drying rice in sunlight illustrates heat radiation and energy transformation. These physical phenomena are integrated with cultural values of gratitude, harmony with nature, and sustainability. The results highlight that ethnophysics can bridge scientific understanding and cultural practice, offering contextual and meaningful learning experiences. By incorporating such traditions into physics education, students can better comprehend scientific principles through real-life cultural phenomena while fostering respect for local heritage. This study concludes that the Wiwit Rice Tradition provides valuable insights into how indigenous practices embody scientific knowledge, supporting the development of culturally responsive and sustainability-oriented science education.